2011
DOI: 10.4081/reumatismo.2008.282
|View full text |Cite
|
Sign up to set email alerts
|

Phytothermotherapy with fermenting alpine grass in knee osteoarthritis: mid-long term results

Abstract: non steroidei e/o trattamenti fisici. L'osteoartrosi del ginocchio, la localizzazione più frequente, è una delle principali cause di disabilità nell'anziano (1, 2) e la principale voce di spesa fra le malattie reumatiche (3). Molti pazienti ricorrono a terapie termali, quali i fanghi, anche perché non sempre i farmaci correnti sono privi di effetti collaterali. Il ruolo dei trattamenti termali è discusso (4), anche se nella Consensus italiana sulle raccomandazioni EULAR 2003 per il trattamento della gonartrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The grass had been mowed and directly baled to be transported to the thermal facility of Garniga (Trento, Italy, S 23°38′57″; W 46°37′19″) where the PTB process was carried out following the protocol described by Narduzzi et al 7 . The facility has four 20 m 3 stainless steel open baths ( Fig. 7) and is designed to host about 1 ton of grass for each cycle in each bath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The grass had been mowed and directly baled to be transported to the thermal facility of Garniga (Trento, Italy, S 23°38′57″; W 46°37′19″) where the PTB process was carried out following the protocol described by Narduzzi et al 7 . The facility has four 20 m 3 stainless steel open baths ( Fig. 7) and is designed to host about 1 ton of grass for each cycle in each bath.…”
Section: Methodsmentioning
confidence: 99%
“…Looking at the differences in the days within each batch, the d1, d2 and d3 samples were richer in aliphatic hydrocarbons (heneicosane, hexadecane, tetradecane and 3-methyltridecane), alpha-terpineol, and estragole. By contrast, the d4, d5 and d6 samples were richer in 1-methylnaphthalene, nonanal, 2-nonanone, 3 www.nature.com/scientificreports/…”
Section: Depth Of Samplingmentioning
confidence: 95%
“…Although few researchers have investigated the effects of phytobalneotherapy, in a review of scientific articles published in PubMed and Scopus between 1870 and 2012, four relevant studies were retrieved and it was concluded that hay baths may be useful for patients with rheumatic conditions like chronic osteoarthritis, a degenerative disease characterized by joint pain and loss of function due to cartilage loss, and fibromyalgia, a disorder in which widespread pain and other symptoms are often reported [1]. Among retrieved trials, three of them involved patients with osteoarthritis [5][6][7], while the remaining one involved patients with fibromyalgia [8]. Phytobalneotherapy was mainly reported to be beneficial for pain relief and functional improvement [1].…”
Section: What Evidence Is There?mentioning
confidence: 99%
“…In another observational study, Miori et al 24 reported the long-term efficacy of one cycle of PTT in a group of patients affected by gonarthrosis, in comparison with the outcome of a conventional medical treatment and physiokinesitherapy (FKT). A total of 142 patients with primary knee OA were included in the study: 54 patients (group 1) were treated with a single course of PTT, 58 patients (group 2) continued with their usual outpatient care, and 30 patients (group 3) were treated with a course of FKT.…”
Section: Clinical Studies In Oamentioning
confidence: 99%